Hydrogen-rich gas enhanced sprint-interval performance: Metabolomic insights into underlying mechanisms - Dong, G.; Liu, H.; Chen, Y.; Bao, D.; Xu, W.; Zhou, J. (Nutrients, 2024)
(1) Background: The diversity of blood biomarkers used to assess the metabolic mechanisms of hydrogen limits a comprehensive understanding of its effects on improving exercise performance. This study evaluated the impact of hydrogen-rich gas (HRG) on metabolites following sprint-interval exercise using metabolomics approaches, aiming to elucidate its underlying mechanisms of action.